2002
DOI: 10.1101/gad.990702
|View full text |Cite
|
Sign up to set email alerts
|

FGF signaling pathways in endochondral and intramembranous bone development and human genetic disease

Abstract: Over the last decade the identification of mutations in the receptors for fibroblast growth factors (FGFs) has defined essential roles for FGF signaling in both endochondral and intramembranous bone development. FGF signaling pathways are essential for the earliest stages of limb development and throughout skeletal development. In this review, we examine the role of FGF signaling in bone development and in human genetic diseases that affect bone development. We also explore what is presently known about how FG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
662
2
22

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 815 publications
(699 citation statements)
references
References 254 publications
13
662
2
22
Order By: Relevance
“…FGF8 is known to have an important role in osteoblastic development and bone formation (Ornitz and Marie, 2002). This suggests that the RA-dependent loss of CAK phosphorylation of RARa induces FGF8 to regulate osteosarcoma cell differentiation.…”
Section: Ra-mediated Rara Hypophosphorylation Induces Fgf8f Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…FGF8 is known to have an important role in osteoblastic development and bone formation (Ornitz and Marie, 2002). This suggests that the RA-dependent loss of CAK phosphorylation of RARa induces FGF8 to regulate osteosarcoma cell differentiation.…”
Section: Ra-mediated Rara Hypophosphorylation Induces Fgf8f Expressionmentioning
confidence: 99%
“…Although many studies have shown that FGF8 regulates osteoblast development and bone formation (Ornitz and Marie, 2002;Jackson et al, 2006), the distinct physiological functions of different FGF8 isoforms in such regulations are unknown. We find that both RA and RARaS77A induce FGF8f expression in U2OS cells (Figure 6f; Supplementary Figure 2A, 7B-E and 8C-E).…”
Section: Ra-mediated Rara Hypophosphorylation Induces Fgf8f Expressionmentioning
confidence: 99%
“…FGFR3 activation leads to phosphorylation and nuclear localization of Stat-1, -5a, and -5b in chondrocytes (Su et al, 1997;Li et al, 1999), while Stat3 is activated by FGFR3 in cell culture (Hart et al, 2000). FGFR3 mutations in humans cause a spectrum of achondroplasias (reviewed in Ornitz and Marie, 2002;Chen and Deng, 2005;L'Hote and Knowles, 2005).…”
Section: Stat Proteins Act Upstream Of Tcfap2amentioning
confidence: 99%
“…The cellular and molecular events underlying craniofacial formation are complex, but there is a growing appreciation that the growth and patterning of the facial primordia has many parallels with development of the limb buds (Mariani and Martin, 2003;Niswander, 2003;Tickle, 2003;Helms et al, 2005). The genetic defects responsible for several human craniofacial syndromes are often accompanied by limb defects (Wilkie and MorrissKay, 2001;Ornitz and Marie, 2002;Thyagarajan et al, 2003;Zelzer and Olsen, 2003;Chen and Deng, 2005;L'Hote and Knowles, 2005), and mutations in a number of mouse genes can also cause morphological alterations in both the face and the limbs (Richman and Lee, 2003;Helms et al, 2005). In molecular terms, the two developmental systems rely on a combination of sonic hedgehog (shh) and fibroblast growth factor (FGF) signals to impart both survival and polarity information (Hu et al, 2003;Mariani and Martin, 2003;Niswander, 2003;Richman and Lee, 2003;Tickle, 2003;Abzhanov and Tabin, 2004;Helms et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…17,18 Gain-of-function mutations have been identified in different dominant autosomal human skeletal disorders such as hypochondroplasia, achondroplasia, and thanatophoric dysplasia. [22][23][24] FGFR3 mutations identical to those found in these disorders have been reported in multiple myelomas, cervix and bladder cancer, colon cancer, and benign skin tumors. [25][26][27][28][29][30][31][32][33] This gene constitutes a promising marker in the clinical management of patients with low-grade, non-muscle-invasive bladder tumors.…”
mentioning
confidence: 98%